The impact of biofuels policy on crude oil refineries - George, S (Oxford Institute for Energy Studies, 2013)
Since 2009, oil refiners in the Atlantic Basin have shuttered more than 3.4 million barrels of daily refining capacity in response to the region’s declining oil demand. While much of this demand decline has been driven by recession and is unlikely to return anytime soon, a significant part of it can be attributed to the rising supply of biofuels. Government mandates are ensuring a rising demand for biofuels in the face of declining absolute fuel demand, with Atlantic Basin refiners caught in the balance.